Effect of Incorporating Computerized Insulin Dose Adjustment Algorithms into a Remote Patient Monitoring Program on HbA1c Levels in Patients with Type 2 Diabetes - Pulicharam, Juvairiya; Davidson, S. Joshua; Bubb, Chard; Evans, Steven; Davidson, Mayer B. (Medical Research Archives, 2022)
Aims : To evaluate the effect of Federal Drug Administration-cleared computerized insulin dose adjustment algorithms (CIDAAs) incorporated into a Remote Patient Monitoring (RPM) program on HbA1c levels. Material & Methods : Type 2 patients receiving insulin for >6 months with HbA1c levels ≥8.0% enrolled in a Medicare Advantage plan were recruited into 3 arms; Group A (RPM plus CIDAAs, N=40), Group B (RPM but no CIDAAs, N=42), and Group C (usual care with no RPM or CIDAAs, N=33).  In Groups A and B, glucose readings of >200 mg/dL and <70 mg/dL triggered alerts and health educators contacted patients for counseling to avoid future episodes. Results : Baseline HbA1c levels (% ± SD) were not statistically different among Groups A (9.5 ± 1.5), B (9.2 ± 1.1) and C (9.0 ± 0.9).  At 6 months, HbA1c levels fell twice as much in Group A (-1.5 ± 1.0) as in Groups B (-0.7 ±1.5) and C (-0.7 ± 1.2) (P <0.001).  Alerts >200 mg/dl were significantly less in Group A (N=942) than in B (N=1111) (P = 0.002) but alerts <70 mg/dL were not significantly different (235 vs 209).  In Group A, baseline per patient daily insulin doses of 78 units rose 40% to 109 units.  Six patients in Group C had emergency room visits for hypoglycemia but none in Groups A and B. Conclusions: The RPM program lessened clinical hypoglycemic risk but required CIDAAs to markedly increase insulin doses effectively and safely to significantly lower HbA1c levels twice as much as either RPM alone or usual care.